Tadzkirah Model in Learning Islamic Religious Education - Sahri Sahri (EDUCATIO : Journal of Education, 2021)
This article discusses the tadzkirah model in learning Islamic religious education. The purpose of this study is to determine the tadzkirah model that is implemented in the learning process of Islamic religious education. The approach used in this study uses library research or library research, by collecting various kinds of primary and secondary sources to support this research. Islamic education has been around since time immemorial and Rasulullah SAW has also taught directly to wives, friends and so on. In this era of industrial revolution 4.0, Islamic religious education must continue to be encouraged and not to fade, let alone confuse in the learning process. Therefore, the learning process must really be designed and designed to achieve a learning goal by applying the tadzkirah learning model. By using the tadzkirah learning model, it is hoped that learning for students both at school, at home or in other environments will help shape the child's personality so that it has the character and nature that has been given by Allah SWT since birth.